2011
DOI: 10.1590/s2176-94512011000300013
|View full text |Cite
|
Sign up to set email alerts
|

Análises microbiológicas de alicates ortodônticos

Abstract: Objective: To evaluate bacterial contamination of orthodontic pliers used in an academic setting. Methods: Thirty-four pliers were selected -17 band remover pliers and 17 bird beak pliers. The control group was composed of 3 previously autoclaved pliers of each model. After use, the pliers in the experimental group were immersed in 10 ml of brain-heart infusion (BHI) culture medium for 2 minutes, incubated at 37º C for 24 to 48 h and seeded in duplicates in different agar-based solid culture media to detect an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 11 publications
(13 reference statements)
2
5
1
2
Order By: Relevance
“…Bacterial colonization was confirmed in all the orthodontic brackets received from different manufacturers. The outcome of the current investigation was similar to prior studies using different orthodontic appliances, such as arch wires [1], orthodontic pliers [6], brackets [11], orthodontic buccal tubes [4], and tooth brushes [13] received from different manufacturers. These studies indicate that orthodontic appliances used in dentistry are often contaminated with bacteria.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Bacterial colonization was confirmed in all the orthodontic brackets received from different manufacturers. The outcome of the current investigation was similar to prior studies using different orthodontic appliances, such as arch wires [1], orthodontic pliers [6], brackets [11], orthodontic buccal tubes [4], and tooth brushes [13] received from different manufacturers. These studies indicate that orthodontic appliances used in dentistry are often contaminated with bacteria.…”
Section: Discussionsupporting
confidence: 75%
“…In our study, Staphylococci were the predominant organisms isolated from orthodontic brackets. Contamination with Staphylococci mostly occurs due to skin contact during manufacturing and/or packaging of orthodontic appliances [1, 6]. Similar studies conducted in this regard reported that Staphylococci were the common organisms to contaminate the orthodontic brackets [1, 3, 14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Відомо, що ротова порожнина містить свій мікробіом, до якого може входити різноманітна патогенна флора, як наприклад Streptococcus mutans, Streptococcus sanguinis, Staphylococcus aureus та Porphyromonas gingivalis [1]. Наслідком використання застарілих методів стерилізації є збільшення захворюваності на інфекції верхніх дихальних шляхів, в патогенезі яких суттєву роль відіграють Mycobacterium tuberculosis, а також деякі бактеріальні штами роду Staphylococcus and Streptococcus [3].…”
Section: вступunclassified
“…Відповідно до сучасних протоколів інструменти класифікують згідно трьох категорій за ризиком інфікування. Критична позиція передбачає використання стерилізаційних процедур для усіх категорій інструментів, через їх контакт із біологічними рідинами та тканинами [3].…”
Section: вступunclassified